Post-transplant pediatric kidney Hypertension - Garcia, Clotilde Druck; Bittencourt, Viviane de Barros; Antonello, Jerônimo Sperb; Krüger, Filipe Dari; Lumertz, Magali Santos; Koltermann, Vanessa; Comparsi, Eduardo Pflug; Stein, Airton; Garcia, Valter Duro (Brazilian Journal of Transplantation, 2007)
Purpose: To determine the prevalence of post-renal transplantation hypertension in a pediatric renal transplant population at Complexo Hospitalar Santa Casa, characterizing the group and verifying associated risk factors. Patients and methods: Data was analyzed in a retrospective cohort of pediatric renal transplant recipients who were grafted before the age of 18. For statistical analysis, the Pearson correlation coefficient was used, with correction of continuity. Hypertension was assumed if BP was above the 95 percentile. Results: 150 patients transplanted for the period between July 1991 and September, 2005 were enrolled. 58% were males. Mean age at transplantation was 10,4 years, and patients had a mean age of 15.5 years at the time of the data collection. There was a prevalence of Caucasians (89.3%). Mean follow-up time was 57.9 months. Immunosuppressant therapy included tacrolimus (68.2%), cyclosporine (27.7%), and sirolimus (4%) with no calcineurin inhibitors. Steroids were used in 86% of patients. Hypertension was present in 86 (57.3%) patients. There was no significant difference in the prevalence of hypertension related to gender, race, donor (living or deceased), graft function, and follow-up time. HTN was present in 52.5% patients receiving tacrolimus, 63.4% in those receiving cyclosporine (p=0,1). In the group on steroids, 62.8% were hypertensive versus 23.8% in the steroid-free group (p=0.002). Conclusion: Hypertension is prevalent after renal transplantation. The use of steroids in kidney transplant recipients is a risk factor to develop hypertension. No other risk factor for high blood pressure was identified.